Evaluating the Fun School Movement (GSM) Using the Discrepancy Evaluation Model in Junior High Schools - Zamzami Zamzami; Widowati Pusporini; Ghany Desti Laksita; Ade Putri Juliati; Muhammad Zawil Kiram (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to evaluate the implementation of the Fun School Movement (GSM) program at public junior high schools in Kulon Progo Regency. The evaluation assesses the achievements and barriers within four key components of GSM: learning environment, pedagogical practices, character development, and school connectedness. The method used is Provus' Discrepancy Evaluation Model (DEM) with a mixed-methods approach, involving 3 principals, 28 teachers, and 288 students. Data were collected through interviews, observations, questionnaires, and document reviews, and analyzed using qualitative analysis and descriptive statistics. The results show that the GSM program successfully created a more positive learning environment, with an average achievement of 75.64% across the three schools, and supported student character development, with an average score of 77.92%. However, the main challenges included varying levels of understanding among teachers, low parental involvement, and the need for further teacher training. The implications of this study emphasize the need for continuous teacher training and increased parental involvement to support the more effective and sustainable implementation of GSM.